2015
DOI: 10.1021/nn5066028
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Differentiation of Adipose-Derived Stem Cells Using Combinatorial Graphene Hybrid-Pattern Arrays

Abstract: Control of stem cell fate by modulating biophysical cues (e.g., micropatterns, nanopatterns, elasticity and porosity of the substrates) has emerged as an attractive approach in stem cell-based research. Here, we report a method for fabricating combinatorial patterns of graphene oxide (GO) to effectively control the differentiation of human adipose-derived mesenchymal stem cells (hADMSCs). In particular, GO line patterns were highly effective for modulating the morphology of hADMSCs, resulting in enhanced diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 51 publications
1
122
0
Order By: Relevance
“…The exceptional electrical conductivity of graphene has been exploited for a range of applications, but thorough investigation of how stimulation of pristine graphene affects cell behaviour is lacking in the literature. A recent paper by Kim et al demonstrated that patterned graphene substrates can preferentially encourage osteogenic or neurogenic differentiation when presented as columns or grids, respectively 12 . However, the cells used in this study were pre-differentiated toward either an osteoblastic or neuronal lineage and the graphene was reduced to graphene oxide, which is known to change the conformation and functionality of adsorbed proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The exceptional electrical conductivity of graphene has been exploited for a range of applications, but thorough investigation of how stimulation of pristine graphene affects cell behaviour is lacking in the literature. A recent paper by Kim et al demonstrated that patterned graphene substrates can preferentially encourage osteogenic or neurogenic differentiation when presented as columns or grids, respectively 12 . However, the cells used in this study were pre-differentiated toward either an osteoblastic or neuronal lineage and the graphene was reduced to graphene oxide, which is known to change the conformation and functionality of adsorbed proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to confirm that the process of engineering did not compromise the ability of the AD-MSCs to differentiate, we compared the ability of engineered and unengineered control AD-MSCS to differentiate along an osteogenic lineage. Briefly, to induce differentiation along this lineage, the engineered or unengineered AD-MSCs were exposed to osteogenic differentiation media for three weeks (Figure S5) [43]. After this differentiation period, osteogenic differentiation was quantified via Alizarin Red S (ARS) staining, which is typically used to evaluate calcium deposited by cells in culture, and qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have proved the ability of GO to promote stem cell differentiation into osteogenic, cardio, neuronal, and adipogenic lineages. [140][141][142][143] Of particular note is the recent work by Kim et al 33 in which a novel strategy to guide stem cell differentiation into specific cell lineages by employing combinatorial GO hybrid-patterns of specific geometries was reported. NGO combinatorial pattern-arrays, with different sizes and geometries, were successfully transferred to various substrates such as Au-coated glass, molded polystyrene, flexible polydimethylsiloxane, and even biodegradable poly(lactic-coglycolic acid) film.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…13 GO contains a large amount of hydrophilic groups on its edge or basal planes; thus, sheets of small size and lower concentrations should be much more biocompatible. These properties make GO extremely attractive to a large swath of scientists with new applications in the fields of drug delivery, [14][15][16][17][18][19][20][21][22][23][24][25] parasitology, 26,27 tissue engineering (TE), [28][29][30][31][32][33][34][35] antibacterials, [36][37][38][39][40][41][42][43][44] cancer therapy, [45][46][47][48][49] sensors [50][51][52][53][54][55][56][57][58][59][60][6...…”
Section: Introductionmentioning
confidence: 99%